(untitled) (PerCursos, 2021)
What would happen if our bodies spoke, if our gagged mouths screamed the silence of all those centuries? Grada Kilomba in The memory of the plantation shows us that through the creation of a new decolonial language it is possible to reconstruct the structures of power and that marginalized identities can then reconfigure the notion of knowledge. We know that the modern patriarchal system has historically colonized our narratives, our languages, which are untranslatable to colonizers, with language being a regulatory ideal. bell hooks on And I’m not a woman? describes how the literature was effective in creating an imaginary of black bodies. Lugones tells us how the modern colonial gender process imprisons Latin American bodies, or even, as Lélia Gonzalez calls it, Amerifricans. Based on these voices and decolonial feminist thinking, I defend the urgency that we have to create a new language, escaping the grammatical restrictions that pervade gender, sexuality and raciality, these categories being interwoven. It is necessary to take a position of authors and not of objects, to narrate our own history, giving way to another vocabulary, denouncing our silences, our colonizing gags masks, our tortured voices, our broken languages, imposed languages, im-peded speeches. Writing is, therefore, an act of resistance and a collective and political hun-ger to gain a voice. I propose a work that is both a political discourse and a personal and poetic narrative, which places the precariousness, the pain, the emotion, the experiences of the Amerifrican corporations incorporated in the discourse and which breaks with the mod-ern capitalist colonial logic, and which also patriarchal.